Analysis of Critical Thinking Levels of Prospective Science Teachers in Ethnoscience Learning Based on Reflective and Impulsive Cognitive Styles - Yasir*, Mochammad; Dwiyanti, Lusiana (Jurnal Pendidikan Sains Indonesia, 2023)
Previous research has not found the right formula to win bull races studied in ethnoscience learning so that it requires problem solving. Solving this problem requires critical thinking skills which can be viewed from reflective and impulsive cognitive styles during bull races. This study aims to determine the level of critical thinking in science teacher candidates based on reflective and impulsive cognitive styles in ethnoscience learning. This type of research is a mix method with exploratory sequential design. The research was carried out in the Science Education Study Program FIP UTM, Bangkalan Regency by taking a sample of 6 science teacher candidate subjects. Data collection was collected using tests, documentation, and interviews. The results of the cognitive style test showed that science teacher candidates were 25% reflective, 29% impulsive, 25% fast-accurate, and 21% slow-inaccurate. The results of this study indicate that reflective science teacher candidates are able to recognize images well, be careful, think deeply so that answers tend to be correct and answer questions according to questions in ethnoscience learning. Impulsive science teacher candidates are able to recognize pictures poorly, are not careful, do not think deeply so that answers are not precise and answer questions at random in ethnoscience learning. The conclusion obtained is that the critical thinking level of reflective science teacher candidates is better than impulsive in ethnoscience learning, although there are not many significant differences.